Rasulullah SAW the Pioneer of Literacy in The Muslim Community of Mecca - Ari Fauzi Rahman (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
AbstractAfter the messenger of Allah (Rasulullah Saw) was sent, the first revelation that was revealed Qs. al-‘Alaq 1-5 which was delivered by Gabriel or Jibril when Rasulullah was sleeping in Cave of Hira. But because of the fear of Rasulullah Saw, come down Qs. al-Muddatsir [74]: 1-2 with the order to wake up and give a warning to the people around you. However, the prophet found some obstacles, namely the condition of the Arabian people of Mecca at that time still adhering to paganism and polytheism as well as the Arab society that was less intellectual, as evidenced by the lack of the Arab Makkah community who could write and read. There were 17 men and 5 women who could write and read at the time. Seeing the condition of the Arabian community of Mecca who was ignorant, the Prophet Muhammad made his preaching secretly by inviting his wife, family, closest friends and servants. Finally the Prophet Muhammad received 38 people embraced Islam, and made Darul Arqam as the center of scientific teachings of Islam for the first time. Darul Arqam is the house of a friend named Arqam ibn Arqam. The efforts of the Prophet to preach the true revelations and the desire to form a literary Arab society finally paid off. After the war, the Prophet Muhammad Saw captured 70 people, the aim of which was to find prisoners who could read and write to teach the Muslim community at that time. After Darul Arqam as the center of teaching of monotheism and accepting people who wished to convert to Islam, the Prophet developed a kuttab that had previously existed but was less interested. Kuttab was used as a place for teaching reading and writing for Muslim communities at that time. Thus there is a difference in the curriculum of the two educational instutions developed by Rasulullah Saw.